(3cTa GdXdGe Yf hLhg TQGFY GdESdGes - (3eMSf Hf eQJVi Hf bGSe, J (B1238 (3g`s ((3eMeO QVG Hf eMeO GdMSfGhjs)
(3ChdgG (B:s
(3GdebOeI GdQGHYI(B... (3aj LfS dHGS GdeUdj(B...s
(3BNQgG (B:s
(3QGLY Edi GdeDPf ZjQ GdeNGda cfGSj HYV aUhd GdBPGf(B... (3hbO JbO Odjdg hGddg CYde ajeG jCJj heG JbOe(B. (3JeJ GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis